Analysis of the impact of the use or non-use of neonicotinoids in agriculture - Ionuţ Laurenţiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Neonicotinoids are a class of chemical insecticides derived from nicotine. Like nicotine, neonicotinoids act on certain types of receptors in nerve synapses. They are much more toxic to invertebrates, such as insects, than to mammals and birds. The popularity of neonicotinoids for pest control is their water solubility, which allows them to be applied to the soil and taken over by the plants. The present paper will present, analyse and evaluate the impact of the use of these insecticides in the agriculture of Romania. In the first phase of the study, we will present the overall situation of the main cultures for which these neonicotinoids are used, by qualitative and quantitative analysis of data from local, national, European and international databases. In the second phase the effect and effort of the use or non-use of these insecticides in agriculture will be estimated. Thus, the difference in production will be determined in an untreated and treated one, and we will see the value of the neonicotinoids in production, on the other hand, the less positive effects of the use of these types of insecticides, namely pollution, or what they call some "ecological disaster", but also its effect on apiculture and implicitly on bees. This study will be pertinent and objective, without favoring or disfavoring any person or institution in these two areas.
Keywords: Q15; Q52; Q57; 330; neonicotinoids; effect; effort; agriculture; apiculture